The Role of HER2-Targeted Therapy in HER2-Positive Metastatic Breast Cancer : A Systematic Review of Randomized Controlled Trials - Muhamad Luthfi Asyhar; Yuke Aulia Novianti; Mia Maya Aziza; Bernita Nur Cahyani; Theresia Murniwati Situmorang; Zia Faradila; Risa Rahmadina; Charles Sanjaya (The Indonesian Journal of General Medicine, 2026)
Introduction: Human epidermal growth factor receptor 2 (HER2) amplification characterises approximately 15–20% of invasive breast carcinomas and was historically associated with rapid visceral dissemination, central nervous system (CNS) tropism, and short survival. Over two decades, HER2-directed monoclonal antibodies, antibody–drug conjugates (ADCs), and tyrosine kinase inhibitors (TKIs) have progressively redefined the natural history of HER2-positive metastatic breast cancer (MBC). This systematic review was undertaken to synthesise, within a single comprehensive evidence framework, the magnitude, consistency, and safety trade-offs of HER2-targeted therapy across all treatment lines. Methods: A systematic review of randomized controlled trials (RCTs) was conducted in accordance with PRISMA 2020. Eligible studies were phase II or III RCTs enrolling adults with HER2-positive advanced or MBC receiving at least one HER2-targeted agent. Two reviewers independently screened, extracted data, appraised risk of bias using Cochrane RoB 2, and rated certainty with GRADE. Effect estimates (hazard ratios [HRs] and risk ratios [RRs]) were pooled using DerSimonian–Laird random-effects inverse-variance models. Results: Twenty-three RCTs comprising 9,808 randomized patients met eligibility. Across 18 trials, the pooled progression-free survival (PFS) HR for HER2-directed intensification versus control was 0.55 (95% CI 0.48–0.63; p<0.001; I²=79.9%). Domain-specific PFS estimates were 0.56 (95% CI 0.47–0.66) for escalation of HER2 blockade, 0.47 (95% CI 0.34–0.64) for ADC-based strategies, and 0.49 (95% CI 0.29–0.83) for next-generation TKIs versus lapatinib. Pooled overall survival (OS) across 12 trials favoured HER2-targeted intensification (HR 0.75, 95% CI 0.69–0.81; p<0.001; I²=13.0%), with domain estimates of 0.69 (95% CI 0.60–0.79) for escalation of blockade and 0.70 (95% CI 0.62–0.79) for ADC strategies. Objective response was significantly improved (pooled RR 1.41, 95% CI 1.09–1.82; p=0.008; I²=85.9%). CNS-specific endpoints, duration of response, clinical benefit rate, and time to quality-of-life deterioration were consistently improved. Tucatinib reduced intracranial progression by 52% (HR 0.48, 95% CI 0.34–0.69; p<0.001) in patients with brain metastases. Symptomatic left ventricular systolic dysfunction remained uncommon (approximately 1–2%), whereas class-specific toxicities—diarrhoea with pan-HER TKIs (grade ≥3 in 24–31%), thrombocytopenia and transaminitis with trastuzumab emtansine (grade ≥3 in 14% and 5%, respectively), interstitial lung disease in 10–15% of trastuzumab deruxtecan recipients, and ocular toxicity with trastuzumab duocarmazine—determined tolerability. Five trials were rated at low risk of bias and 18 raised some concerns, chiefly related to open-label design. Discussion: The evidence demonstrates a coherent dose-of-blockade relationship: every incremental increase in completeness or potency of HER2 pathway inhibition has translated into reproducible gains in disease control and survival. Statistical heterogeneity in PFS was substantial but explicable by line of therapy, comparator potency, and mechanism, rather than discordance in effect direction. Negative or neutral trials (margetuximab, atezolizumab added to trastuzumab emtansine, afatinib) delineate paradigm boundaries, indicating that immune-mediated or non-selective pan-ErbB approaches have not yet matched selective, payload-based, or brain-penetrant strategies. The CNS remains the decisive frontier; tucatinib-based regimens have the strongest randomized support for active brain metastases. Consistency across East Asian populations supports applicability to regional practice, though structural barriers to access and surveillance remain. Conclusion: HER2-targeted therapy produces large, consistent, and clinically meaningful improvements in PFS, OS, and response across all treatment lines in HER2-positive MBC, with a predictable and manageable toxicity profile. Sequential use of dual antibody blockade, ADCs, and brain-penetrant TKIs should be regarded as the standard therapeutic architecture. Equitable access to these agents—together with systematic cardiac and pulmonary surveillance—should be prioritised in health systems where HER2-directed therapy remains incompletely implemented. Future trials should address head-to-head comparisons beyond second line, biomarker-driven allocation, ADC sequencing, and treatment de-escalation in exceptional responders.